Dalla sociologia dei problemi sociali ad alcuni problemi (sociali e non) della sociologia: la lezione di Kitsuse e Spector - Recchi, Luca (SocietàMutamentoPolitica, 2018)
This essay is intended to be an analytical reflection on the two essays with which Kitsuse and Spector introduced and outlined their proposal for a sociology of social problems. The level of investigation is the theoretical and epistemological one concerning some central questions of the constructionist proposal as formulated by the two authors. Starting from the distinction between social conditions and social problems, the theoretical investigation tries to develop the consequences in terms of defining the very activity of the sociologist and his own field of work. In this sense, questions concerning the role of the sociologist in society are touched upon, as are some limits of his operational practice regarding the activities of ordinary social life. Finally, according to the argumentative path followed, a recontextualization of the criticism of ontological gerrymandering is proposed; the idea is that the linguistic formulation of the aims of the sociology of social problems does not make an incorrect argumentative move if it is framed within the form of social life in which it is expressed.